Prevalence and the impact of hypogammaglobulinemia in newly diagnosed chronic lymphocytic lymphoma patients - Namrata Singh; Sarah L. Mott; Grerk Sutamtewagul; Ashley McCarthy; Susan L. Slager; James R. Cerhan; Zuhair Ballas; Brian K. Link (eJHaem, 2020)
Abstract Objective To examine the prevalence of hypogammaglobulinemia in chronic lymphocytic lymphoma (CLL) patients and to test the hypothesis that patients with hypogammaglobulinemia have a distinct clinical profile and outcome. Methods Immunoglobulin levels (IgA, IgG, IgM, IgE) were measured in newly diagnosed, treatment naïve banked samples of 150 patients with CLL followed prospectively for outcomes. Cox regression models were used to assess the effects of clinical variables on overall survival (OS). Results The median age of the selected CLL cohort was 64 years with a male predominance; 96.2% of the patients were white. Fifty‐nine deaths occurred during a median follow up of 6.8 years. Hypogammaglobulinemia in CLL was common in our cohort with 88 (58.7%, 95% CI: 50.4‐66.6%) patients having a measurable isotype deficiency. The most common Ig deficiency was IgM (44.0%). IgA deficiency or low IgE was associated with higher Rai stages as well as with higher white blood cell counts at presentation. Any immunoglobulin deficiency was not associated with overall survival. Conclusion A significant proportion of treatment‐naïve CLL patients had underlying Ig deficiencies – both in isolation and in isotype combinations. Although a deficiency of IgA or IgE was associated with more severe disease at presentation, the impact of this association was mild.